High-efficiency methanogenesis via kitchen wastes served as ethanol source to establish direct interspecies electron transfer during anaerobic Co-digestion with waste activated sludge. (1st June 2020) - Li, Yang; Tang, Yapeng; Xiong, Pu; Zhang, Mingqian; Deng, Qingling; Liang, Dandan; Zhao, Zhiqiang; Feng, Yujie; Zhang, Yaobin
Abstract: Kitchen wastes (KW) have been widely investigated for bio-ethanol production, while no study utilizes KW as ethanol source to stimulate the methanogenic communities to perform direct interspecies electron transfer (DIET), since the excess acidity contained after the biological ethanol-type fermentation pretreatment (BEFP) can seriously inhibit the DIET-based syntrophic metabolism. In this study, a strategy that utilized waste activated sludge (WAS) as co-substrate to relieve the excess acidity after BEFP during anaerobic co-digestion (AcoD) was proposed. The results showed that, under the mixed ratio of 1:2 and 1:5 (KW:WAS, volume ratio), both methane production and organic compound removal evidently increased, compared with that treating the sole WAS. Conversely, under the other mixed ratios (sole KW, 5:1, 2:1 and 1:1), no methane but the evident hydrogen production was detected, and syntrophic metabolism of organic acids and alcohols was prevented. Three-dimensional excitation emission matrix (3D-EEM) analysis showed that the protein-like organic compounds contained in both KW and WAS were effectively degraded. Furthermore, the maximum methane production potential from WAS during AcoD (260.5 ± 4.1 and 264.3 ± 2.7 mL/g-COD) was higher than that treating sole WAS (250.8 ± 0.1 mL/g-COD). Microbial community analysis showed that, some genera capable of metabolizing the complex organic compounds with the reduction of the elemental sulfur or equipped with the electrically conductive pili were specially enriched during AcoD under the mixed ratio of 1:2 and 1:5. They might proceed DIET with methanogens, such as Methanosarcina and Methanospirillum species, to maintain the syntrophic metabolism effective and stable, since the abundance of both Methanosarcina and Methanospirillum species evidently increased. Graphical abstract: Image 1 Highlights: Kitchen wastes (KW) as bio-ethanol source were used to establish DIET. Waste activated sludge (WAS) relieved excess acidity in KW after ethanol production. Degradation of both KW and WAS was enhanced during anaerobic co-digestion. Some sulfur-reducing genera and genera equipped with e-pili were specially enriched. Abundance of both Methanosarcina and Methanospirillum significantly increased.